Chemical and structural stability of La0.6Sr0.4Co0.2Fe0.8O3−δ ceramic vs. medium/high water vapor pressure. Issue 10 (December 2015) - Upasen, Settakorn; Batocchi, Pierre; Mauvy, Fabrice; Slodczyk, Aneta; Colomban, Philippe
Abstract: During the last decades, perovskite-type oxides have received large attention as potential electrolytes and electrodes for Solid Oxide Fuel Cells (SOFC), including Proton Ceramic Fuel Cells (PCFC), gas separation membranes and High Temperature Steam Electrolysers (HTSE). A thermal treatment in an autoclave, at a temperature close to an operating temperature, was used to measure the chemical stability of La0.6 Sr0.4 Co0.2 Fe0.8 O3− δ (LSCF6428) ceramic under medium and high water pressure (~20 and 40 bar). This mixed ionic−electronic conductor (MIEC) exhibits interesting properties as cathode of fuel cell materials. The reactivity rate of the investigated LSCF6428 sample under the protonation process conditions (several weeks at 550 °C using CO2 -free and CO2 -saturated water) was studied in order to evaluate a potential use of this compound. Bulk and surface structural/chemical changes were characterized by optical microscopy, TGA, dilatometry, Raman and ATR-FTIR spectroscopy. The results revealed only minor surface modifications in the case of ceramic treated under medium vapor pressure (20 bar) using CO2 -free water. On the contrary, under higher pressure (40 bar) and CO2 -saturated water several second phases were detected, namely strontianite, cobalt oxides and hematite. The chemical/structural stability of LSCF6428 is compared with previously investigated Rare-Earth nickelate ceramics: La2 NiO4+ δ / Pr2 NiO4+ δ / Nd2 NiO4+ δ .